Sistem Alat Bantu Jalan bagi Penyandang Tuna Netra dengan Menggunakan Algoritma Fuzzy - Hera Tartila; Oscar Hadikaryana (Journal Data Science, Technology, Informatics and Security, 2024)
In this study, the authors developed an automatic walking assistance system for visually impaired individuals to support their mobility and daily activities. The system is designed to detect obstacles or objects located in front of, to the left of, and to the right of the user while walking. It utilizes an Arduino Nano as the main microcontroller and ultrasonic sensors to detect surrounding obstacles. When an obstacle is detected, the system automatically provides warning signals to the user. Feedback is delivered through an audible alert generated by a buzzer integrated into the walking cane, enabling visually impaired users to recognize the presence of obstacles and navigate more safely.